Myocarditis and inflammatory bowel diseases: A single-center experience and a systematic literature review. (1st April 2023) - Giordani, A.S.; Candelora, A.; Fiacca, M.; Cheng, C.; Barberio, B.; Baritussio, A.; Marcolongo, R.; Iliceto, S.; Carturan, E.; De Gaspari, M.; Rizzo, S.; Basso, C.; et al.
Abstract: Background: Myocarditis and inflammatory bowel diseases (IBD) are rare conditions, but may coexist. Myocarditis in IBD may be infective, immune-mediated, or due to mesalamine toxicity. A gap of knowledge exists on the clinical features of patients that present myocarditis in association with IBD, especially for endomyocardial biopsy-proven cases. Our aims are: 1) to describe the clinical characteristics of patients with an associated diagnosis of myocarditis and IBD in a single-center hospital, 2) to perform a systematic review of the literature of analogous cases. Methods: We retrospectively analyzed data of patients followed up at the outpatient Cardio-immunology and Gastroenterology Clinic of Padua University Hospital, to identify those with an associated diagnosis of myocarditis and IBD. In addition, a systematic review of the literature was conducted. We performed a qualitative analysis of the overall study population . Results: The study included 104 patients (21 from our single center cohort, 83 from the literature review) . Myocarditis in IBD more frequently affects young (median age 31 years) males (72%), predominantly with infarct-like presentation (58%), within an acute phase of the IBD (67%) and with an overall benign clinical course (87%). Nevertheless, a not negligible quote of patients may present giant cell myocarditis, deserve immunosuppression and have a chronic, or even fatal course. Histological evidence of mesalamine hypersensitivity is scarce and its incidence may be overestimated. Conclusions: Our study shows that myocarditis in association with IBD, if correctly managed, may have a spontaneous benign course, but predictors of worse prognosis must be promptly recognized. Graphical abstract: Unlabelled Image Highlights: Myocarditis and IBD may coexist, raising concerns for prognosis and management. Myocarditis associated to IBD generally has a spontaneous benign course. A sizable quote of patients deserve immunosuppression and have a severe prognosis. Mesalamine toxicity should be investigated, if myocarditis presents during IBD.